EXPERIMENTAL CARDIOVASCULAR AND LUNG RESEARCHA novel high vacuum chest drainage system – a pilot study - Mrówczyński, Wojciech; Tille, Jean-Christophe; Khabiri, Ebrahim; Giliberto, Jean-Pierre; Courvoisier, Delphine S.; Kalangos, Afksendiyos; Walpoth, Beat H. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Background: To assess the safety and feasibility of use of a novel high vacuum chest drainage system (HVCDS) and its influence on the cardiovascular system compared to a conventional system (CCDS). Material and methods : Five anesthetized pigs underwent a median sternotomy. Three drains were placed in retrocardiac, retrosternal and left pleural positions. The animals received a HVCDS (22 Fr with 180 2-mm holes, n = 2) or a CCDS (n = 2). In the fifth animal off pump coronary artery bypass graft (OPCABG) stabilizers were tested. After chest closure animals had three 30 min runs of artificial bleeding (5 ml/min) under different negative aspiration pressures (–2, –20, –40 kPa) for both groups, followed by standardized surgical bleeding (–40 kPa – HVCDS, – 2 kPa – CCDS). Hemodynamic parameters and each drain’s output were registered every 5 minutes and the residual blood was assessed. All catheters, the heart and left lung underwent macroscopic and histopathological examination. Results: The application of the different pressures showed neither hemodynamic changes nor differences in blood drainage with both systems in two bleeding models. The HVCDS enabled drainage comparable to the CCDS but showed relevant clotting. Application of –20 kPa and –40 kPa caused macroscopic epicardial and pulmonary lesions in all tested devices including OPCABG stabilizers consisting of sub-epicardial or sub-pleural hemorrhage without myocyte or alveolar damage. Conclusions: The novel and conventional chest drainage systems used at pressures up to 40 kPa induced no hemodynamic instability. Both systems showed adequate equal drainage, despite major HVCDS clotting. High negative pressure drainage with both systems showed focal sub-epicardial and sub-pleural hemorrhage. Thus, long-term assessment of high pressure drainage and potential interaction with fragile structures (coronary bypass graft) should be carried out.